Computational approach to target USP28 for regulating Myc. (April 2020) - Chakravorty, Debangana; Ghosh, Abhirupa; Saha, Sudipto
Abstract: Myc is a crucial player in cellular proliferation and a known regulator of cancer pathobiology. Modulation of Myc expression targeting the Myc Protein-Protein Interactors (PPIs) like Myc-Max has till now been the most explored approach. However, this approach threatens the normal cells where Myc expression is required for proliferation. This demands the need for a new strategy to indirectly modulate Myc expression. Indirect modulation can be achieved by regulating Myc turnover. FBXW7 mediates the ubiquitination and subsequent degradation of Myc which is reversed by USP28. In this study, the interaction of USP28 with FBXW7 as well as with its substrate, Ubiquitin (Ub) were used as targets. Computation based high-throughput screening of bioactive small chemicals using molecular docking method was implemented to predict USP28 inhibitors. For the two regions, docking study with AutoDock Vina gave top 10 best scoring drugs which were identified and tabulated. The two regions defined in the study as FBXW7 binding and Ub binding also encompass the areas in which USP28 differed from USP25, a homologue with a different role. Out of these the best scoring drugs were explored for their role in cancer, if any. This study was performed keeping in mind re-purposing of these known drugs for possible alternative anti-Myc cancer therapy.